Analysis of volumetric changes following endodontic therapy in teeth with apical periodontitis utilizing cone beam computed tomography periapical volume index: A retrospective observational study - Reshma Rajasekhar; Kailash Attur; Sooraj Soman (Saudi Endodontic Journal)
Introduction: The fundamental goal of endodontic treatment revolves around the prevention and treatment of apical periodontitis (AP). Several indices based on two-dimensional and three-dimensional imaging systems have been developed for assessing AP. The primary objective of this study was to evaluate the volumetric changes in periapical lesion following endodontic therapy adopting cone-beam computed tomography periapical volume index (CBCTPAVI) using a semi-automatic segmentation software for lesion segmentation and volume calculation. Materials and Methods: This study included pretreatment and follow-up CBCT images of 33 permanent teeth with pulpal necrosis and AP of patients who had endodontic treatment from the department of conservative dentistry from February 2022 to August 2023. ITK SNAP software were used for periapical lesion segmentation from CBCT images and CBCTPAVI were assigned based on calculated lesion volume. Pretreatment and posttreatment lesion volume and CBCTPAVI were compared using the Wilcoxon signed-rank test. Results: There was no significant difference between pretreatment and posttreatment CBCTPAVI scores (P = 0.240); however, a significant difference was seen when lesion volume was compared (P < 0.001). Conclusion: Lesion healing can be clearly appreciated in terms of volume by utilizing segmentation software.